Assessment of Ukraine’s counterterrorism security based on the Global Terrorism Index - Kuchmenko, Vitalii (Public Policy and Accounting, 2025)
The article provides a detailed analysis of the Global Terrorism Index, which covers more than 163 countries around the world, representing a significant portion of the world’s population. The paper illustrates and analyzes: the top 10 countries with the highest level of terrorist activity according to the Global Terrorism Index for 2025; countries with a high level of terrorism according to the Global Terrorism Index in 2025; countries with moderate levels of terrorism according to the Global Terrorism Index in 2025; countries with low levels of terrorism according to the Global Terrorism Index for 2025; the level of terrorist activity in African countries according to the Global Terrorism Index for 2025, etc. The Sahel region of Africa, south of the Sahara, is now the epicenter of terrorism, with the Sahel accounting for more terrorist deaths in 2022 than South Asia, the Middle East, and North Africa combined. In 2022, the number of deaths in the Sahel accounted for 43 percent of the global total, compared to just one percent in 2007. Of particular concern are two countries, Burkina Faso and Mali, which accounted for 73 percent of terrorism deaths in the Sahel in 2022 and 52 percent of all terrorism deaths in sub-Saharan Africa. North America had the largest regional improvement in its score, while sub-Saharan Africa recorded the largest decline. North America consists of two countries, the United States and Canada, neither of which has a high score; however, it is the only region where no country has a zero GTI score. In the West, the number of attacks has continued to decline since 2017, decreasing every year. In 2022, there were 40 attacks, which is 27 percent less than the 55 attacks in 2021. However, the number of deaths has more than doubled, albeit from a low base, from nine deaths in 2021 to 19 in 2022, with 11 of those occurring in the US. This was the first increase in deaths from terrorist attacks in the West since 2019. In Europe, Islamist extremists carried out two attacks in 2022. Attacks in the US remain low, with only eight attacks recorded in 2022. None was attributed to any known terrorist group. This year, there have been only four attacks and no deaths in the UK, the first year since 2014 with no deaths recorded, while Germany has seen the lowest number of attacks since 2015. The state of Ukraine’s counterterrorism security was assessed based on the Global Terrorism Index. The results of the study are of practical importance for shaping national policy in the law enforcement sphere, developing EU technical assistance programs, and improving the effectiveness of managing European integration processes in the post-war period.